2022
DOI: 10.1136/bmjopen-2021-058912
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing rate after optimal near-patient C-reactive protein testing in acutely ill children presenting to ambulatory care (ARON project): protocol for a cluster-randomized pragmatic trial

Abstract: IntroductionChildren become ill quite often, mainly because of infections, most of which can be managed in the community. Many children are prescribed antibiotics which contributes to antimicrobial resistance and reinforces health-seeking behaviour. Point-of-care C reactive protein (POC CRP) testing, prescription guidance and safety-netting advice can help safely reduce antibiotic prescribing to acutely ill children in ambulatory care as well as save costs at a systems level.Methods and analysisThe ARON (Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…On the other hand, a review of Verbakel et al [8] stated that POC CRP test in ambulatory care accompanied by clinical guidance can reduce the immediate antibiotic prescribing rate, and another study showed that normal CRP levels discourage immediate antibiotic prescribing, even when EBM practice guidelines advise differently, and elevated CRP levels did not increase antibiotic prescribing [21]. Currently the EPIcentre team, led by Prof. Dr. Jan Verbakel, is performing a multicentre, cluster-randomized trial in ambulatory care, in which the impact of a diagnostic algorithm, including clinically guided POC CRP testing and safety netting advice on antibiotic prescribing rate and the further management of acutely ill children is investigated [50].…”
Section: Practical Implementation and Implications For Researchmentioning
confidence: 99%
“…On the other hand, a review of Verbakel et al [8] stated that POC CRP test in ambulatory care accompanied by clinical guidance can reduce the immediate antibiotic prescribing rate, and another study showed that normal CRP levels discourage immediate antibiotic prescribing, even when EBM practice guidelines advise differently, and elevated CRP levels did not increase antibiotic prescribing [21]. Currently the EPIcentre team, led by Prof. Dr. Jan Verbakel, is performing a multicentre, cluster-randomized trial in ambulatory care, in which the impact of a diagnostic algorithm, including clinically guided POC CRP testing and safety netting advice on antibiotic prescribing rate and the further management of acutely ill children is investigated [50].…”
Section: Practical Implementation and Implications For Researchmentioning
confidence: 99%
“…None of the studies or the review used the phrase “safety-netting”; hence their omission from the aforementioned literature review. Newer trials have started adopting the term 9. However, the inconsistencies in previous studies, plus the fact that these patient leaflets contain other information besides safety-netting advice, and the variable verbal content in the trial arms, mean the effectiveness of the leaflets cannot directly be attributed to safety-netting alone.…”
mentioning
confidence: 99%